(untitled) (Global Journal of Computer Science and Technology, 2015)
The goal of this literature review is to compare and contrast contemporary strategic management theories Additionally the secondary goal is to evaluate the implications for strategic information technology management Management of people is the direct control of human motivation and behavior Human motivation like behavior is complex and a science unto itself Human motivation theory seeks to understand human motivations and therefore understand human behavior to a level such that predictions can be made The study of human motivation has a background or base in physiological behavioral cognitive and social sciences However those existing disciplines are not sufficient alone or combine to study this complex topic The behaviors linked to human motivation are linked to very evolutionarily basic aspects of our biology despite the advanced cognitive abilities of man The ability to predict human motivation and behavior is very important to companies and organizations as they are always seeking new strategies to motivate and respond to the needs of their employees